Doping Polypyrrole Films with 4-N-Pentylphenylboronic Acid to Enhance Affinity towards Bacteria and Dopamine. - Mohsen Golabi; Laurence Padiolleau; Xi Chen; Mohammad Javad Jafari; Elham Sheikhzadeh; Anthony P F Turner; Edwin W H Jager; Valerio Beni (PLoS ONE, 2016)
Here we demonstrate the use of a functional dopant as a fast and simple way to tune the chemical affinity and selectivity of polypyrrole films. More specifically, a boronic-functionalised dopant, 4-N-Pentylphenylboronic Acid (PBA), was used to provide to polypyrrole films with enhanced affinity towards diols. In order to prove the proposed concept, two model systems were explored: (i) the capture and the electrochemical detection of dopamine and (ii) the adhesion of bacteria onto surfaces. The chemisensor, based on overoxidised polypyrrole boronic doped film, was shown to have the ability to capture and retain dopamine, thus improving its detection; furthermore the chemisensor showed better sensitivity in comparison with overoxidised perchlorate doped films. The adhesion of bacteria, Deinococcus proteolyticus, Escherichia coli, Streptococcus pneumoniae and Klebsiella pneumoniae, onto the boric doped polypyrrole film was also tested. The presence of the boronic group in the polypyrrole film was shown to favour the adhesion of sugar-rich bacterial cells when compared with a control film (Dodecyl benzenesulfonate (DBS) doped film) with similar morphological and physical properties. The presented single step synthesis approach is simple and fast, does not require the development and synthesis of functional monomers, and can be easily expanded to the electrochemical, and possibly chemical, fabrication of novel functional surfaces and interfaces with inherent pre-defined sensing and chemical properties.